World Migration Report 2011 - International Organization for Migration (United Nations, 2012)
This report presents available evidence on public perceptions and attitudes regarding migration globally. It analyzes how they can influence and be influenced by policy and the media. It suggests several ways to improve communication about migration to promote better understanding and recognition of the benefits of migration. The publication comprises two parts: part A analyses major migration trends in 2010/2011, offering an overview of developments in policy, legislation, international cooperation and dialogue on migration, and part B reviews the evolution of the agency’s approach to migration management since the end of the Cold War. It also presents a statistical overview of the organization’s programmes over the last decade.